Deconstructing development discourse : buzzwords and fuzzwords - Eade, Deborah; Cornwall, Andrea, 1963- (Warwickshire, U.K. : Practical Action Pub in association with Oxf am GB, 2010)
"Writing from diverse locations, contributors critically examine som e of the key terms in current development discourse. Why should languag e matter to those who are doing development? Surely, there are more urg ent things to do than sit around mulling over semantics? But language d oes matter. Whether emptied of their original meaning, essentially vacu ous, or hotly contested, the language of development not only shapes ou r imagined worlds, but also justifies interventions in real people's li ves. If development buzzwords conceal ideological differences or sloppy thinking, then the process of constructive deconstruction makes it pos sible to re-examine what have become catch-all terms like civil society and poverty reduction, or bland aid-agency terms such as partnership o r empowerment. Such engagement is far more than a matter of playing wor d games. The reflections included here raise major questions about how we think about development itself"--Publisher's website.
"This volume is based on Development in Practice, Volume 17, Numbers 4 & 5"--T.p. verso.
Includes bibliographical references and index.
Keywords: Development economics; Development economics -- Language